Case report: Imaging of septic arthritis in the hip joint of a calf treated with femoral head ostectomy - Tsuka, Takeshi; Okamoto, Yoshiharu; Nishiyama, Atsushi; Sunden, Yuji; Morita, Takehito (Frontiers in Veterinary Science, 2024)
A 24-day-old male Japanese Black calf presented with weight-bearing lameness in the left hind limb and a swollen pelvis. Ultrasonography revealed the accumulation of fluidity materials with a mixture of hyper-and hypo-echogenicity, enclosed by 5-10-mm-thick capsular structures. On the ventraldorsal radiograph of the pelvis, irregular and radiolucent osseous changes were evident in the femoral head and acetabulum within the swollen hip joint, with soft-tissue density. Computed tomography (CT) confirmed the relationship between the bony and soft tissue lesions, which was suspected following ultrasonography and radiography, and provided additional findings, such as intra -articular accumulation of gas and the degree of osteolytic changes. Based on the imaging findings and cytology of the arthrocentesis specimen, the patient was diagnosed with hip arthritis and osteomyelitis of the femoral head. Additionally, the severity of the lesions supported our decision to perform a femoral head ostectomy. The postoperative radiographic and CT findings of the treated pelvis were helpful in evaluating the efficacy of this technique. Following treatment, the animal could walk and showed normal development, although it was three postoperative months before weight-bearing lameness improved. To the best of our knowledge, this is the first report to describe the combined use of ultrasonography, radiography, and CT in the diagnosis, preoperative planning, and evaluation of the postoperative effects of bovine hip arthritis. Additionally, this report details the therapeutic efficacy of femoral head ostectomy for bovine hip arthritis, a technique that has not been reported previously.